2010
DOI: 10.1159/000321224
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Comparing Jejunal Pouch and Jejunal Interposition Reconstruction after Proximal Gastrectomy

Abstract: Background/Aims: The incidence of proximal gastric cancer is increasing, so proximal gastrectomies are often performed to preserve gastric function, but the optimal reconstruction method after surgery remains controversial. We therefore conducted a prospective pilot study comparing reconstructions using jejunal pouch interposition or jejunal interposition. Methods: Thirty-eight patients with early proximal gastric cancer were included in this study. Equal numbers of patients were randomly assigned for reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 46 publications
0
37
1
2
Order By: Relevance
“…In a more recent publication, where the EORTC QoL questionnaires were used, both short-term and functional results were similar after a Merendino reconstruction as compared to Ivor-Lewis procedure [33]. On the other hand, proximal gastrectomy with jejunal interposition in patients with non-advanced gastric cancer, which is a procedure similar to the Merendino, seems to have a superior functional outcome compared to total gastrectomy with RNY reconstruction [23, 24]. Obviously the importance of objectively assessing long-term data also in corresponding patient cohorts is warranted to assess the clinical place of the Merendino procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent publication, where the EORTC QoL questionnaires were used, both short-term and functional results were similar after a Merendino reconstruction as compared to Ivor-Lewis procedure [33]. On the other hand, proximal gastrectomy with jejunal interposition in patients with non-advanced gastric cancer, which is a procedure similar to the Merendino, seems to have a superior functional outcome compared to total gastrectomy with RNY reconstruction [23, 24]. Obviously the importance of objectively assessing long-term data also in corresponding patient cohorts is warranted to assess the clinical place of the Merendino procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal gastrectomy with jejunal interposition for non-advanced proximal gastric cancer, which is similar to the Merendino procedure, is performed mainly in the Far East and has been shown to induce fewer post gastrectomy symptoms as compared to total gastrectomy with Roux-en-Y reconstruction, without adding more postoperative complications [23, 24]. Therefore, the Merendino procedure may have the potential to offer significant advantages in challenging post-fundoplication situations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a retrospective comparative study revealed that the food intake volume and QOL in the short term were significantly better in patients who underwent JPI after proximal gastrectomy than in those who underwent Roux-en-Y reconstruction after total gastrectomy 2) . Furthermore, both retrospective and prospective randomized studies of the short-and medium-term postoperative results rated JPI after proximal gastrectomy better than simple jejunal interposition after proximal gastrectomy 8,13,14) . However, a retrospective study from a single center claimed that esophagogastrostomy and fundoplication after resection of the upper half of the stomach was a better strategy than jejunal interposition, with or without a pouch, because the rate of occurrence of surgical complications was significantly lower after esophagogastrostomy 15) .…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for the better short-term outcomes after esophagogastrostomy in that study could be the fundoplication. However, it should also be taken into account that the volume of the remnant stomach differed among studies 8,[13][14][15] , and this will significantly affect how easily the surgery can be performed and the postoperative outcomes 14) . Thus, we consider that jejunal interposition with or without pouch formation remains a viable option for reconstruction, especially when the remnant stomach is small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation